CORRELATION BETWEEN THE INDEX AND EFFICIENCY INDICATORS OF SUCCESS IN RECREATION TABLE TENNIS - Miran Kondrič; Joško Sindik; Nicolae Ochiana (University of Banja Luka, Faculty of physical education and sport, 2012)
Amongst different methods of quality analysis of the table tennis player's game, the basic idea of this study was to detect those indicators (data) for collection of which only the final result in particular competitions in a larger number of events, of one game, or certain sets in one table tennis game would be sufficient. The basic aim of the research is to establish to what extent the indexes and variables derived directly from the results of individual table tennis games could predict indexes which are described by the final result for an individual in a larger number of individual table tennis games. The research involves an analysis of an intentional sample of 956 table tennis players competing in various leagues during 2007. Results show that correlations between individual variables of the table tennis competitors' efficiency are statistically significant. The correlations between indexes of the competitor's efficiency are also statistically significant. In particular, we found positive (and significant) correlations between all the direct and indirect indicators of players' efficacy (medium strongly to strongly correlated). The correlation between individual variables and indexes of the table tennis competitor's efficiency, with the total efficacy index, are statistically significant. It can be concluded that all the indexes and variables can describe specific aspects of the performance in table tennis, predicting total efficacy of the players.